Use of PowerPoint And Kahoot ! For Increase Motivation Study Student At SMPN 01 Pelalawan - Ghefira Auliya Rabbani Anedin (Lembaga Pengembangan Kinerja Dosen, 2024)
This service activity aims to explore the use of Power Point and Kahoot as learning motivation tools for students at SMPN 01 Pelalawan. A qualitative descriptive approach was used in this research, with data collected through online surveys and direct interviews with 10 selected respondents. The research results show that the use of PowerPoint and Kahoot received a positive response from students, with more than half of respondents expressing enjoyment and enthusiasm for the learning supported by both platforms. This integration of technology enables the creation of engaging and effective learning experiences, leading students towards a more enjoyable and results-oriented learning transition.